Implementación de relés programables en módulos de práctica de controles eléctricos. - Gonzalez Murillo, Ghian Jeshua (2019)
This thesis project was developed for the creation of modules with Programmable Relays, for the Electrical Controls laboratory of the Technical Faculty for the Development of the Santiago de Guayaquil Catholic University, due to the lack of resource of these, for that was the motive that inspired me to develop this thesis project. The descriptive research methodology used in this thesis will help to understand the operation and use of the Programmable Relay, as well as the additional materials and tools required to perform the practice with Programmable Relay. In the process, an investigation was made about the Programmable Relay: its parts, connections, programming, applications and its management in practice in order to increase and implement this equipment in the Electric Controls Laboratory. A manual proposal for the operation of the programmable relay is presented as an initiative for student learning. In addition to this in the practices used engines which was given the respective maintenance to a three-phase motor of twelve terminals, through this the student can use the engine without any problem in any practice that the teacher requires.